2023
DOI: 10.3389/fimmu.2023.1070076
|View full text |Cite
|
Sign up to set email alerts
|

Do proton pump inhibitors alter the response to immune checkpoint inhibitors in cancer patients? A meta-analysis

Abstract: IntroductionGut microbiota can significantly affect the effectiveness of immune checkpoint inhibitors (ICIs) in cancer patients. Recently, antibiotics were shown to decrease survival rate of patients treated by ICIs. Proton pump inhibitors (PPIs) can indeed modulate microbiota’s diversity, therefore altering ICIs response. A meta-analysis was performed based on published data to verify this hypothesis.MethodsIn this study, over 41 publications, exploring the impact of concomitant PPI treatment on outcomes of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 85 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…In recent years, several retrospective studies have suggested that there may be a potential interference of concomitant medications, such as steroids, antibiotics, and proton pump inhibitors (PPIs), with immunotherapy outcomes. Particularly, a history of PPI administration at the beginning of treatment or during treatment has been associated with worse outcomes in patients receiving ICIs, especially anti-PD-L1 (programmed cell death 1 ligand 1) agents . PPI might change the composition of the gut microbiome due to the downstream translocation of oral commensals, thus altering its immunomodulating properties and impairing ICI activity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, several retrospective studies have suggested that there may be a potential interference of concomitant medications, such as steroids, antibiotics, and proton pump inhibitors (PPIs), with immunotherapy outcomes. Particularly, a history of PPI administration at the beginning of treatment or during treatment has been associated with worse outcomes in patients receiving ICIs, especially anti-PD-L1 (programmed cell death 1 ligand 1) agents . PPI might change the composition of the gut microbiome due to the downstream translocation of oral commensals, thus altering its immunomodulating properties and impairing ICI activity.…”
mentioning
confidence: 99%
“…In fact, as recently demonstrated by Derosa et al, a precise equilibrium of symbiotic bacteria with the right relative abundance of Akkermansia muciniphila (ie, <4.799%), is more associated with ICI outcomes in patients with NSCLC than PD-L1 levels, although the type of bacteria might play a role as well. Some of these studies provided conflicting results or remained inconclusive due to their small sample size and retrospective nature, although a recent large meta-analysis by Lopes et al conducted of 20 042 patients with different tumors treated with ICIs concluded that progression-free survival (PFS) (hazard ratio [HR], 1.28; 95% CI, 1.15–1.42) and OS (HR, 1.37; 95% CI, 1.23–1.52) were negatively associated with PPI. Nevertheless, whether PPIs are associated with immunotherapy response is still to be prospectively determined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although extensive research is aiming at identifying tumour-associated or host-related factors predicting for ICI efficacy or tolerability, most of them are immutable and intrinsic to the patient and the disease, thus potentially impossible to be manipulated (e.g., PD-L1 expression levels) or very hard to be meaningfully modified in a relatively short timeframe (e.g., body mass index) ( 129 ). Similarly, the use of some drugs (e.g., antibiotics, proton-pump inhibitors and obviously steroids) has been shown to impair ICI efficacy in retrospective studies ( 130 ). Yet, most likely these drugs have been prescribed for a therapeutic reason and arguably it would not be easy to avoid them altogether in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PPI-induced hypochlorhydria may affect the gut microbiota, potentially influencing the efficacy of immunotherapy. Several studies have reported worse outcomes with the combination of PPIs and ICIs in various cancers, including NSCLC, melanoma, urothelial carcinoma, renal cell carcinoma, and hepatocellular carcinoma [22]. This combination may also increase the risk of immune-related adverse events, particularly acute kidney injury.…”
Section: Interaction Of Ppis and Cancer Treatmentmentioning
confidence: 99%